Jobs in Global Value Chains : New Evidence for Four African Countries in International Perspective - Pahl, Stefan; Timmer, Marcel P.; Gouma, Reitze; Woltjer, Pieter J. (World Bank, Washington, DC, 2019)
What is the potential for job growth in Africa under participation in global value chains (GVCs)? In this study the concept of GVC jobs is introduced which tracks the number of jobs associated with GVC production of goods. A novel decomposition approach is used to account for GVC jobs by three proximate sources: global demand for final goods, a country's GVC competitiveness (measured as the country's share in serving global demand) and technology (workers needed per unit of output). Based on newly assembled data, it is shown how GVC jobs and incomes have changed over the period 2000-14 in Ethiopia, Kenya, Senegal and South Africa, compared to developments in some other low- and middle-income countries in the world. The four African countries stand out in terms of a low share of GVC jobs in the (formal) manufacturing sector, and a relatively high share in agriculture due to strong backward linkages, especially in the case of food production. All countries benefitted highly from growing global demand for final goods. At the same time it appears that technical change in GVCs is biased against the use of labour, greatly diminishing the potential for job growth through GVC participation.